2005
DOI: 10.1002/chem.200400587
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Electrode Approach for Highly Selective Detection of Glucose Based on Diffusion Layer Theory: Experiments and Simulation

Abstract: A dual-electrode configuration for the highly selective detection of glucose in the diffusion layer of the substrate electrode is presented. In this approach, a glassy carbon electrode (GCE, substrate) modified with a conductive layer of glucose oxidase/Nafion/graphite (GNG) was used to create an interference-free region in its diffusion layer by electrochemical depletion of interfering electroactive species. A Pt microelectrode (tip, 5 microm in radius) was located in the diffusion layer of the GNG-modified G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…It is regarded that BDD thin film electrodes are inert for glucose oxidation [12,28]. However, some groups reported that glucose could be oxidized at metal-implanted BDD thin film electrodes [13,19,29] and bare BDD thin film electrode treated with the hydrogen flame [30], and similar types of CV curves were obtained, i.e., the forward and backward sweeps of CV curves have a same oxidation peak at about + 0.63 V vs. SCE and superpose nearly completely to each other.…”
Section: Electrochemical Detection Of Glucose In Basic Solutionsmentioning
confidence: 99%
“…It is regarded that BDD thin film electrodes are inert for glucose oxidation [12,28]. However, some groups reported that glucose could be oxidized at metal-implanted BDD thin film electrodes [13,19,29] and bare BDD thin film electrode treated with the hydrogen flame [30], and similar types of CV curves were obtained, i.e., the forward and backward sweeps of CV curves have a same oxidation peak at about + 0.63 V vs. SCE and superpose nearly completely to each other.…”
Section: Electrochemical Detection Of Glucose In Basic Solutionsmentioning
confidence: 99%
“…The electropolymerization of TBO on electrode surface has been reported in detail elsewhere [37,38]. A mediator glucose biosensor immobilizing glucose oxidase at electropolymerized PTBO film on carbon nanotube modified glass carbon electrode has been reported [39].…”
Section: Preparation and Electrochemical Characterization Of The Gc/cmentioning
confidence: 99%
“…In recent years, Xia's group proposed and developed a concept of electrochemical depletion of electroactive species in diffusion layer for selective detection [1][2][3][4]. The depletion of interfering reactive species in the diffusion layer is a simple and reproducible method, which opens a new direction for interferent-depleted electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Xia's concept was first established with selective glucose detection in the presence of AA by adopting an SECM configuration of the two working electrodes to achieve overlapping of the diffusion layer [1,2]. The substrate electrode was served as an interferent-depleted micro-circumstance, while the tip electrode was used for detecting glucose by sensing hydrogen peroxide formed during the process of the oxidization of glucose on the glucose oxidase layer-coated substrate electrode.…”
Section: Introductionmentioning
confidence: 99%